Characteristics of Edible Film Made from Dangke Whey and Agar Using different Percentage of Glicerol - . Fatma; R. Malaka; M. Taufik (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2015)
Composites of whey dangke and agar can form edible film. The downside of this edible film are fragile, brittle and inflexible. Addition of glycerol, which is one of plasticizers, may improve characteristics of edible film to be more elastic, flexible and not easy to become fragile. The proper use of glycerol will affect the characteristics of the edible film. The purpose of this study was to determine the effect of the percentage of glycerol to the edible film characteristics, including yield, thickness, tensile strength, elongation, and color. This study was carried out according to completely randomized design consisted of three levels of glycerol concentrations, i.e. 25%, 35%, and 45% as treatments. Each treatment was repeated 5 times. The results study indicated that the thickness of edible film ranged from 0.024 mm to 0.035 mm, the yield varied from 7.26% to 7.87%, the tensile strength was between 13.60 and to 4.20 N, elongation was from 33.33 to 80%, and the color of L was 88.86 to 88.81, the value for “a” was between (-1.48) and (-0.94), and “b” was from 4.19 to 5.56. An increase in the percentage of glycerol decreased tensile strength but increased elongation. The addition of 45% glycerol caused “a” color change value (reduced green color). The addition of 35% glycerol caused changes in color values “b” (reduced yellow color), but the increase in the percentage of glycerol did not change the thickness and brightness values (L) of edible film. It was concluded that the higher the percentage of glycerol added in manufacturing edible film made from a composite whey dangke and agar decreased the tensile strength, increased the elongation and changed the color values of “a” and “b”, but did not change the thickness and rendemen of edible film.